Incentives for Corporate Environmental Information Disclosure in China: Public Media Pressure, Local Government Supervision and Interactive Effects - Jia Xue (Sustainability, 2021)
Disclosing environmental information is essential for listed firms to demonstrate social conscience. To fulfill government and public media supervision, Chinese listed firms are increasing the quality and quantity of disclosed environmental information. This elicits a new topic of interest: the correlation between media/government supervision and corporate environmental information disclosure (EID). The paper addresses this issue through data analysis and factor correlation study in data from some high-pollution firms in China during 2017–2019. The study first introduces a standardized definition for the quantification of media and government supervision, as well as the degree to which the corporation discloses the environmental information. Then, the correlations between the factors are isolated and refined to three sub-topics: (1) how public media and local government supervision affect the quality of corporate EID; (2) how is the interactive effect of public media and government supervision related to corporate EID; (3) how is the distinct ownership of corporate affect the government supervision on corporate EID. The concluding result from the above factor analysis could provide guidance for authorities to adjust certain laws and regulations so that the media and government supervision better motivates the corporate EID, and furthermore, better sustainable development of ecological environment.